ALQURAN DALAM PERDEBATAN PEMAHAMAN TEKSTUAL DAN KONTEKSTUAL - Sadik, M. (Hunafa: Jurnal Studia Islamika, 2009)
The Qur’an, the holy scripture of the Muslims, never changes since its  revelation. However, qur’anic exegesis, as the results of brilliant thoughts of the interpreter can only differ from one another. The difference of qur’anic exegesis may be brought about by methods of interpreting the qur’anic verses. Generally speaking, there are method of interpreting the qur’anic verses; textual interpretation and contextual interpretation. These two methods of interpretation have been employed from the time of the Prophet Muhammad to the present time.Kata Kunci: Alquran, pemahaman tekstual, pemahaman kontekstual